Performance characterization of a novel PV/T panel with nanofluids under the climatic conditions of Muscat, Oman - Afzal Husain; Nabeel Z. Al-Rawahi; Nasser A. Al-Azri; Mohammed Al-Naabi; Musaab El-Tahir (International Journal of Renewable Energy Development, 2023)
The study presents an experimental analysis of a novel mini channels-based Photovoltaic/Thermal (PV/T) panel with nanofluid flow. The design consists of a PV plate attached to an aluminum substrate absorber plate having minichannels grooved on it to act as a solar collector and cooling mechanism for PV. The proposed design was tested for thermal and electrical efficiencies under the working fluids of water, Al2O3, and SiO2 nanofluids at 0.1% and 0.2% concentrations in water and at a flow rate of 0.005 l/s to 0.045 l/s. The experiments were carried out outdoors in a real environment and the measurements were taken for PV surface and fluid temperatures, incidence solar flux, electrical voltage, and current produced. The PV and PV/T performance was compared, and a noticeable enhancement in electrical efficiency was observed with the proposed design as compared to the bare PV module, and an appreciable augmentation in thermal efficiency was noticed when nanofluids were applied. The maximum electrical and thermal efficiencies of PV/T with 0.2% Al2O3 nanofluid were 19.1% and 73.4%, respectively; whereas for bare PV panels, the electrical efficiency was 18.7%. The Al2O3 nanofluid at 0.2% exhibited more than a 10% increase in thermal efficiency compared to water as a working fluid in PV/T.